Potential of Binahong Leaf Extract (Anredera cordifolia) for Anemia Treatment in Anemic Rat Model - Dewajanti, Anna Maria; Stephanus, Chealsea A.; Mano, Ivanna G; Purnamawati, Purnamawati; Rumiati, Flora; Sumbayak, Erma Mexcorry; Limanto, Agus (Faculty of Medicine, Universitas Padjadjaran, 2025)
Anemia, characterized by low hemoglobin (Hb) and erythrocyte counts, can be induced by reactive oxygen species (ROS) or known as hemolytic anemia. Binahong (Anredera cordifolia) has been explored for its potential in managing anemia; yet, its efficacy against ROS-induced anemia remains under investigated. This study, conducted from January to May 2023, aimed to evaluate the potential of Binahong leaf extract (BLE) in treating anemia caused by oxidative stress. Anemia was induced by administering NaNO2 to 24 rats (Rattus norvegicus), followed by the administration of BLE at doses of 50,100, and 200 mg/kgBW for seven days. Hemoglobin levels were measured using Sahli method and erythrocytes count were determined using a Hemocytometer at three stages: pre anemia (HA), before-treatment (H0), and after-treatment (H7). Results showed that BLE significantly increased the Hb level by 1.3g/dL (p=0.000), 3.87g/dL (p=0.034), and 4.53g/dL (p=0.016) at 50 mg/kgBW, 100mg/kgBW, and 200 mg/kgBW, respectively, after treatment. Additionally, a dose of 200 mg/kgBW significally increased the erythrocyte count by 3.84 x 106 L/mm3 (p=0.033). These findings suggested that BLE has the potential to improve Hb levels and erythrocyte counts in ROS-induced anemia, indicating a promising natural approach to managing anemia.